EVALUASI PENGGUNAAN ANTIBIOTIK DENGAN METODE GYSSENS PADA PASIEN PNEUMONIA DI RUMAH SAKIT BHAYANGKARA KUPANG PERIODE JULI – DESEMBER 2019 - Yusuf, Muhammad; Auliah, Nielma; Sarambu, Hana Evangelista (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Pneumonia is a disease in Indonesia that has a high mortality rate in 2018. Pneumonia is an inflammation of the lungs caused by microorganisms (bacteria, viruses, fungi, parasites). Pneumonia caused by Mycobacterium tuberculosis is not included. While lung inflammation caused by non-microorganisms (chemicals, radiation, aspiration of toxic substances, drugs, etc.) is called pneumonitis. One of the treatment for pneumonia is antibiotics where the incidence of resistance in patients often occurs due to irrational use, therefore it needs to be monitored and evaluated by health workers. The purpose of this study was to determine the use of antibiotics in pneumonia patients at Bhayangkara Hospital Kupang with the Gyssens method according to the Minister of Health of the Republic of Indonesia No. 8 of 2015. The Gyssens method is an evaluation of the use of antibiotics to assess the accuracy of the use of antibiotics which includes the accuracy of indications, the accuracy of selection based on effectiveness, toxicity, price and spectrum, duration of administration, dose, interval, route and time of administration. The method used is non-experimental with a descriptive research design, the sample taken is 25 medical record data. The results of the research category 0 (precise and rational) were 84% or in other words the use of antibiotics was rational, category IVb (there were antibiotics that were less toxic) was 12% and in category IIb (inappropriate interval antibiotics) was 4%.